Large enhancement of thermoelectric performance in CuInTe2 upon compression. (June 2018) - Yu, Hao; Chen, Liu-Cheng; Pang, Hong-Jie; Qin, Xiao-Ying; Qiu, Peng-Fei; Shi, Xue; Chen, Li-Dong; Chen, Xiao-Jia
Abstract: Thermoelectric materials can directly generate electric power by converting waste heat, and the efficiency is appraised by the figure of merit zT . A high zT value larger than three is required to achieve comparable efficiency of the traditional heat engines. Despite great efforts for over a century, the desired value of three is seemingly an upper limit, and many existing thermoelectric materials have the zT values less than one. If their zT values can be improved for several times to break through the upper limit, the energy revolution could be expected. Here, a p -type CuInTe2 is chosen as an example to show the extremely important role of pressure in enhancing the thermoelectric performance. Over five times increase of the zT value is realized by the application of pressure. Both the enhancement of the power factor and the reduction of the thermal conductivity account for this large enhancement. The former is due to the optimization of the carrier concentration and band structure, and the latter is attributed to the enhanced phonon anharmonicity. Our results offer an effective method to improve zT of the existing materials for the future technological applications. Graphical abstract: Thermoelectric materials can generate electricity directly from waste heat and are thus considered as renewable energy. The efficiency of a thermoelectric material is described as a dimensionless figure of merit, zT  = σS 2 /κT, where σ is the electrical conductivity, S is the Seebeck coefficient, κ is the thermal conductivity, and T is the absolute temperature. By compressing a p -type CuInTe2 by using diamond anvil cells, the researchers found over five times increase of the zT value at room temperature and high pressures. This finding offers an effective method to improve zT of the existing materials for the future technological applications. Highlights: This is the first systematic experimental study to demonstrate how applying pressure can tune and improve the thermoelectric efficiency. A series of high-pressure techniques are developed to investigate the thermoelectric properties of a material. Large enhancement of zT is achieved by the comprehensive modulations on the electrical and thermal transport properties. Our findings offer an effective method to improve zT of the existing materials for the future technological applications.